ON THE CHOICE OF A MOUNTAIN TOURIST DESTINATION. THE EVALUATION OF DRIVERS BY YOUNG PEOPLE - Viassone, Milena (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2012)
In the last decade the mountains of Cuneo have met difficulties in attracting young tourists. Despite the large literature on drivers considered in the choice of a destination, a few contributions focus on the motivations that account for the choice on the part of young people. This paper, based on the identification of drivers of attractiveness of a tourist destination, investigates how the level of satisfaction of young people influences the quality of the offered services. This objective is achieved by means of a literature review on young-tourist destination and on the measurement of tourist satisfaction, the creation of an adapted SERVQUAL model able to measure the gap between Cuneo’s youth priorities and satisfaction. This is possible throughout an explorative study performed by means of a questionnaire submitted to 200 young tourists. Finally, paths of action have been suggested to provincial Bodies throughout a focus group. Results show how young tourists consider very important: safety, hygiene and intact nature. This is only an exploratory study applied to a single case study but could be applied at other levels (urban, national...) and implemented in comparison with benchmarks.